Embedded finance : when payments become an experience - Sieber, Scarlett; Guibaud, Sophie (John Wiley & Sons, Inc., 2022)
"Sieber and Guibaud provide a comprehensive outlook of the highly anticipated concept of embedded finance and the opportunity it brings to the multitude of players who will have tangible overlap with financial services They highlight the Big Tech companies (Amazon, Google, etc.) and their customers as they have the largest scale but also explore other companies across industries who will benefit from the shift to embedded finance. Embedded Finance is a rather new trend which makes now the perfect time to share the story as it is clear that it is here to stay and will revolutionize the future of the movement of money across sectors as we know it. Over the last decade plus, a first wave of Fintechs (startups entering financial services) have entered the space to launch vertical financial services resulting in the "unbundling of the bank". Shortly after, neobanks (or digital-only banks) were launched, aiming at providing a different approach to banking than what traditional banks offered, by being digital first, and focusing on solving the banking problems or specific target segments (startups, small businesses, students, expats, migrants,...). Those services were the beginnings of a powerful wave, embedded finance. Embedded finance is different because it enables companies across industries (think everything from retailers like grocery to car auctions), with existing audiences, to cater to their customers' financial needs at the point of context. It is an enabler to new revenue streams, engagement and better visibility on data. Most importantly, it equips tech, brands and retailers with the ability to provide a banking and payments experience to their end-customers in a seamless, convenient, and authentic way by providing accounts and loans when they need it most, naturally integrated into the experience. Furthermore, while embedded finance has already gained traction within the digital first world (Vertical software-as-a-service players such as Shopify and Digital Platforms such as Grab), we are just at the beginning of this movement as embedded finance will also enable brands and retailers to provide powerful offline experiences based on ubiquitous payments and finance at the point of use (Amazon Fresh payment-less grocery store in the UK). This new trend will have a strong societal impact, specifically on how consumers experience banking but also on banks' business models moving forward. There are multiple stakeholders who are actively participating in this revolution, including banks, technology players, fintechs, brands, consulting companies, regulators- all for the benefit of the customer. Given what is at stake, embedded finance should be a priority on their strategic agenda. We are on a mission to demonstrate that big tech companies and brands more broadly can and will become a monumental part of the fintech community. Embedded Finance will focus on providing our readers (as outlined below) everything they need to know about this evolving trend, lessons learned from early players, who are the enablers today globally, what role the banks will play, and how embedded finance will impact the future as we know it - for consumers and society as a whole."--